Oblika eritrocita in njegova deformabilnost pri spremenjenih zunanjih pogojih - Smrkolj, Tomaž (Medicinski razgledi, 2000)
Changes in erythrocyte shape are necessary in the circulation of blood, therefore deformability is one of the basic properties of erythrocytes. A research project was conducted in order to determine the role of the submembrane protein skeleton in the mechanical stability of erythrocytes. Our hypothesis suggested that changes in the mechanical properties of the protein skeleton should result in changed deformability of the erythrocyte membrane. The properties affecting the deformability of erythrocytes were determined by observing changes in erythrocyte shape resulting from variations in external factors. Changes in erythrocyte shape were induced using sodium salicylate, which transforms biconcave discs (the physiological shape of the erythrocytes)into echinocytes, i. e. spheres with numerous membrane spicules. Diamide was added to strengthen the submembraneous protein skeleton and shape changes resulting from the addition of sodium salicylate were observed again. The results suggest that diamide lowers the deformability of the erythrocyte membrane. The degree of decrease in deformability depends on diamide concentration. Membrane deformability depends on the mechanical characteristics of the submembrane protein skeleton. Lower deformability is the result of higher skeleton strength.
Keywords: eritrociti; Erythrocytes; oblika; Drug effects; deformabilnost; Erythrocyte deformability; Band 3 protein; Erythrocyte membrane; Sodium salicylate; Diamide